IMPLEMENTATION OF THE WEIGHT PRODUCT METHOD IN THE SYSTEM NEW STUDENT ADMISSION - Siti Nurhasanah Nugraha; Rangga Pebrianto; Fani Nurona Cahya; Irwan Herliawan (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2022)
The development of information technology is something that cannot be separated from life today. The development of information technology, especially the internet, is certainly welcomed by all circles, and has even penetrated the world of education since the last few years, thus creating competitive competition in every educational institution. Currently, there are not many schools in Indonesia that hold new student admissions (PPDB) by utilizing the online system. Of course, this will take a very long time, because after selecting the prospective students, the committee must recap the names and grades of the students accepted. We need a system that will support decisions in the selection of new student admissions so that the resulting output is more accurate. To solve this problem, it is necessary to have a decision support system for the selection process for new admissions using the Weight method Products . With this method the PPDB selection calculation will be more objective because the calculation is based on predetermined weights and assessment criteria. So that the creation of an optimal system that will facilitate the PPDB selection process.